The double-edged role and therapeutic potential of TREM2 in atherosclerosis - Botao Zhu; Yuxuan Liu; Daoquan Peng (Biomarker Research)
Abstract Atherosclerosis is a chronic lipid-driven inflammatory disease characterized by infiltration of large numbers of macrophages. The progression of the disease is closely related to the status of macrophages in atherosclerotic plaques. Recent advances in plaque analysis have revealed a subpopulation of macrophages that express high levels of triggering receptor expressed on myeloid cells 2 (TREM2). Although TREM2 is known to play a critical role in inflammation, lipid metabolism, and tissue repair, its role in atherosclerosis is still not fully understood. Recent studies have shown that TREM2 promotes macrophage cholesterol uptake and efflux, enhances efferocytosis function, regulates inflammation and metabolism, and promotes cell survival, all of which are significant functions in atherosclerosis. In early plaques TREM2 promotes lipid uptake and increases lesion size. In advanced plaques TREM2 promotes macrophage survival and increases plaque stability. The dualistic nature of TREM2 in atherosclerosis, where it can exert both protective effect and a side effect of increased lesion size, presents a complex but crucial area of study. Understanding these dual roles could help in the development of new therapeutic strategies to modulate TREM2 activity and utilize its atheroprotective function while mitigating its deleterious effects. In this review, we discuss the roles and mechanisms of TREM2 during different stages of atherosclerotic plaques, as well as the potential applications of TREM2 in the diagnosis and treatment of atherosclerosis.